Skeleton crew - Ahlberg, Allan (New York : Mulberry Books, 1992)
Three skeletons have a good time on their sailing vacation, until their boat is boarded by pirates.
Keywords: Skeletons-Fiction; Sea stories; Vacations-Fiction; Humurous stories